الدين في عيون الصينيين المعاصرين وضرورة دعوتهم إلى الإسلام (Islam in the View of Contemporary Chinese and the Need to Invite Them to Islam) - الصيني, يونس عبد الله ما تشنغ بين (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
تعد الصين أكبر دولة في العالم من حيث عدد سكانها إذ وصل العدد إلى ألف وثلاثمائة مليون نسمة، وهو يمثل أقل من ربع سكان العالم. وقد صارت هذه الدولة بعد الانفتاح السياسي والإصلاح الاقتصادي قوة عالمية تغزو العالم كله بمنتجاتها المتنوعة، الأمر الذي جعل العالم كله ينظر إليها بإعجاب وتقدير. ومع هذا التقدم الهائل في الجانب المادي أصبح الفراغ الروحي مشكلة كبيرة تقلق قادة الصين السياسيين ومفكريها، وقد أدى هذا الفراغ الروحي مع توفر وسائل إشباع الرغبات الجسدية إلى انتشار الفساد الأخلاقي على جميع المستويات بالرغم من سيادة الفكر الكنفوسى الواقعي على الثقافة الصينية بشكل عام. ومن هنا يحاول هذا البحث معرفة موقف الصينيين المعاصرين من الدين عامة، ومن الإسلام خاصة مستهدفا إلى التعرف على كيفية توصيل نور الإسلام إلى قلوبهم. والبحث يتكون من مقدمة، وأربعة مباحث، وخاتمة مع توصيات. وقد اعتمد الباحث فى جمع المعلومات على المنهج الوصفى والإستقرائى القائم على الملاحظة والتجربة كما اعتمد فى دراسة الموضوع على المنهج التحليلي والنقدي لبيان ضرورة القيام بدعوة الصينيين إلى الإسلام باعتباره المنقذ الوحيد من الضلال والفساد والهلاك. ومن أهم ما توصل إليه الباحث إثبات فشل المبادئ الشيوعية في توجيه سلوك الإنسان، وتنمية القيم، وتأكيد عظمة الإيمان بالله واليوم الآخر في استقامة الإنسان، وتحسين صورته، وتحقيق السعادة الدائمة. الكلمات المفتاحيّة: الدين، الصينيون المعاصرون، الدعوة، الانفتاح السياسي، الإصلاح الاقتصادي، الفكر الكنفوسى، المبادئ الشيوعية. Abstract China is the world's most populous country with a population of 1.3 billion, representing a quarter of the world's population. This country after political openness and economic reformation has become a global force that invades the whole world with its diverse products, which has made the whole world admired and appreciated China. With this tremendous progress on the material side, the spiritual vacuum has become a major problem for the political leaders and thinkers of China. This spiritual vacuum, with the means to satisfy physical desires, has led to the spread of moral corruption at all levels, despite the predominant Confucius thought of Chinese culture in general. Hence, this research attempts to explore the position of contemporary Chinese people of religion in general and Islam in particular, aiming to identify how to connect the light of Islam to their hearts. The research consists of an introduction, four questions, and a conclusion with recommendations. The researcher relied on the descriptive and extrapolation method based on observation and experiment. He also adopted the study of the subject on the analytical and critical method of explaining the need to invite the Chinese to Islam as the only savior of misguidance, corruption and destruction. One of the most important findings of the researcher is to prove the failure of the principles of Communism in guiding human behavior, developing values, and confirming the greatness of faith in Allah and the Last Day in the integrity of man, improving man’s image and achieving lasting happiness. Keywords: religion, contemporary Chinese, advocacy, political openness, economic reformation, Confucius thought, Communist principles.